INTEGRATING AI ART TOOLS IN NATIONAL EDUCATION POLICY - Gaikwad, Baliram N.; Patel, Palak; Bansal, Shubhansh; Chaudhary, Swati; Thakur, Mamta; Fida, Hashmat; Itnal, Vijay (ShodhKosh: Journal of Visual and Performing Arts, 2025)
The fast development of artificial intelligence has brought potent tools of creativity, which are changing the visual arts education all over the world. The implementation of AI art tools into the concept of the National Education Policy (NEP) is a strategic chance to coordinate technological innovation with the innovative goals of creativity orientation, competency focus, and experiential learning. The paper discusses the ways in which AI-driven artistic software (including generative models or intelligent imaging systems or style transfer or AI-assisted critique systems) can be effectively integrated into the formal education process without sacrificing human creativity, cultural identity, and pedagogical integrity. Based on the constructivist theory of learning, the paradigms of the experiential education model, and the human-AI co-creation and learning paradigms, the study conceptualizes AI as the supplementary partner to artistic practice, which promotes ideation, reflections, personalization, and skill building. The framework proposed aligns AI art tools to NEP priorities, such as multidisciplinary learning, creative thinking, digital literacy and inclusive education. This paper introduces a multi-layered architectural design, which includes infrastructure, data, intelligence and application layer to facilitate creative classrooms. The paper also provides policy-level recommendations on the design, assessment, and ongoing evaluation of the curriculum, and stage-by-stage implementation of the process at a national level in terms of teacher training, institutional preparation, and deployment of infrastructure in stages. The key issues that concern data privacy, copyright, ambiguity of authors, algorithmic bias, and cultural sensitivity are discussed in detail with the focus on the protection of indigenous and traditional art forms.